The models of students’ adaptation to online learning in terms of Merton’s theory of anomie - Śliwa, Ewa; Wnek-Gozdek, Joanna (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2022)
The outbreak of the Covid - 19 pandemic resulted in the introduction of restrictions that forced academia to move to a remote mode of education and modify the existing methods of achieving their goals. This situation caused different adaptation reactions in the society. The article presents the problem of students’ adaptation to new conditions of education. The theoretical background is provided by R.K. Merton’s typology of modes of adaptation. The aim of the article is to analyze the adaptation styles of students of different majors. A quantitative strategy was used in the research. A questionnaire survey was conducted among 303 students. The surveyed students showed different ways of adapting to particular elements of remote education, but the most common style was a conformist one.